Protection of natural resources of Sevastopol: an integrated approach to preserving a unique ecosystem - Agalyev D. B. (A breakthrough in science: development strategies, 2025)
The article examines the current problems of protecting the natural resources of Sevastopol. Anthropogenic factors that have a negative impact on the marine and coastal ecosystems, water resources and biodiversity of the region are analyzed. Comprehensive measures are proposed to optimize environmental protection activities, including increased monitoring, the introduction of modern technologies and the improvement of the ecological culture of the population.
Keywords: экологическая безопасность; природные ресурсы; комплексный подход; natural resources; environmental safety; integrated approach; защитные меры; protective measures